TRADITIONAL MUSICAL ART IN THE CONTEXT OF MODERN SOUND SPACE: PROBLEMS OF PRESERVATION AND DEVELOPMENT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines two aspects of the problem of the existence of traditional musical art in the modern sound space. This definition is what development is in relation to the living oral musical tradition, what is subject to development there, what can develop in the structure of musical language, composition, genre, form, what directions can be here that illustrate this process. In theoretical terms, the development of the concept of “development” in relation to Eastern musical art includes two of its components - the improvement of what already exists in musical practice and the creation of new phenomena, the discovery of new paths of development. Another aspect of the stated problem is the influence of the modern sound space on the auditory tuning and perception of a folk musician. Due to objective circumstances, they simultaneously include two different sound systems: modern, with its diversity of genres and types, stylistic trends, principles of sound formation and purely traditional, with its ethnic sound forms of national musical art. Examples from the Tajik musical culture are given, directions for studying this phenomenon are proposed.
Keywords: traditional musical system, development, improvement, creation of new phenomena, folk musician, sound space, auditory tuning, information technologies, two temporary forms of heritage, simultaneity of coexistence of different sound systems.